2013
DOI: 10.1371/journal.pone.0054236
|View full text |Cite
|
Sign up to set email alerts
|

A Single Cell Level Based Method for Copy Number Variation Analysis by Low Coverage Massively Parallel Sequencing

Abstract: Copy number variations (CNVs), a common genomic mutation associated with various diseases, are important in research and clinical applications. Whole genome amplification (WGA) and massively parallel sequencing have been applied to single cell CNVs analysis, which provides new insight for the fields of biology and medicine. However, the WGA-induced bias significantly limits sensitivity and specificity for CNVs detection. Addressing these limitations, we developed a practical bioinformatic methodology for CNVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…The results of the current research confirm that NGS provides highly accurate aneuploidy detection at substantially lower cost than existing methods used for PGS and that testing can be performed within a fresh IVF cycle, avoiding the complication of cryopreservation. A small number of previous studies had suggested that the combination of WGA and NGS might be capable of producing useful genomic data from single cells 12–15. However, previous attempts to harness massively-parallel sequencing methods for the detection of aneuploidy in single cells required several days to complete, meaning that preimplantation genetic testing could only be carried out if embryos were cryopreserved after biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current research confirm that NGS provides highly accurate aneuploidy detection at substantially lower cost than existing methods used for PGS and that testing can be performed within a fresh IVF cycle, avoiding the complication of cryopreservation. A small number of previous studies had suggested that the combination of WGA and NGS might be capable of producing useful genomic data from single cells 12–15. However, previous attempts to harness massively-parallel sequencing methods for the detection of aneuploidy in single cells required several days to complete, meaning that preimplantation genetic testing could only be carried out if embryos were cryopreserved after biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…This processing pipeline was developed into a user-friendly web server platform with impressive visualization tools called Ginkgo (http://gb.cshl.edu/ginkgo). Another copy number method uses SCS read count data generated from DOP-PCR that corrects for GC bias and performs binary segmentation followed by dynamic thresholding (Zhang et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…1A). We successfully phased 131 785 and 133 601 of the maternal and paternal heterozygous sites, including mutations in the hemoglo- bin, beta (HBB) 14 gene. Subsequently, we used an HMM to determine the parental transmission, identifying recombination breakpoints and filtering out sequencing error at the same time.…”
Section: Embryo Haplotype Phasingmentioning
confidence: 99%
“…Concomitantly, the accuracy of the final genotypes stabilized above 97%. This in- 14 Human genes: HBB, hemoglobin, beta; HLA-DRB1, SlC25A22, solute carrier family 25 (mitochondrial carrier: glutamate), member 22; INS, insulin; SMPD1, sphingomyelin phosphodiesterase 1, acid lysosomal; TH, tyrosine hydroxylase.…”
Section: Embryo Haplotype Phasingmentioning
confidence: 99%
See 1 more Smart Citation